ISOLASI DAN KARAKTERISASI SENYAWA BIOAKTIF EKSTRAK DIETIL ETER DAUN MIANA (Coleus scutellarioides (L) Benth) YANG AKTIF TERHADAP BEBERAPA MIKROBA UJI - Nurmaya Effendi (As-Syifaa Jurnal Farmasi, 2010)
Has been conducted research Isolation and characterization of compounds Bioaktif Leaf Extract Diethyl Ether Miana (Coleus scutellarioides (L) Benth) is active against some microbes Test. Maceration extraction is done with diethyl ether. Diethyl ether extracts obtained isolated by method column chromatography with using silica gel as absorbent and hexane-ethyl acetate as dilution fluid, and obtained six fractions. Fraction III-9 was isolated by Preparatif Thin Layer Chromatography (KLTP) and obtained ten tapes.Isolates fraction III-9 identified by chemical reaction with ammonia vapor, aluminum chloride and boric citro, and showed a positive reaction to the flavonoid class of compounds. Data ultraviolet-visible spectroscopy showed a maximum wavelength of 420 nm, while the infrared spectroscopy showed the existence of functional groups - C = C -; - OH; - CH3; and - CH - alifatis and - CH - aromatic. Isolates fraction III-9 with KLT-bioautgraphy was active against  microbial testing Staphylococcus aureus, Candida albicans and Salmonella thyposaKey Words : Leaf Extract Diethyl Ether Miana, Maceration, KLT-Bioautography